Highly sensitive seesaw capacitive pressure sensor based on SOI wafer. Issue 5 (1st February 2014) - Yang, C.C.; Zhao, Q.; Gao, C.C.; Liu, G.D.; Zhang, Y.X.; Cui, W.P.; Hao, Y.L.
Abstract : A novel microelectromechanical system capacitive pressure sensor with two wings, which amplify the mechanical deformation of the pressure sensing diaphragm and increase the sensor's sensitivity, is presented. This seesaw structure is available for both single and differential capacitive pressure sensors. To verify this design, a single capacitive pressure sensor is manufactured based on silicon on a insulator (SOI) wafer. The test result shows that this pressure sensor has a sensitivity of 7.75 fF/kPa.